EFFECT OF EDIBLE COATINGS ON JAPANESE LOQUAT ( Eriobotrya japonica T.) POSTHARVEST QUALITY - Carlos J. MÁRQUEZ C. (Universidad de Antioquia, 2009)
Effect of two edible coatings on the quality of loquat fruit (Eriobotrya japonica T.) from Callosa d’En Sarria (Spain) is studied. The coatings are prepared with commercial solutions of chitosan (0,6%) and sucroester fatty acids (1%), that are applied to fruit at fully-ripe stage, and stored at 20°C and 90% RH for 16 days. Gas chromatography is used to find the rate of respiration and ethylene production. Firmness is determined with a universal machine (Instron Machine Model 4302, Canton Mass, USA®). Physiological weight loss is measured gravimetrically, and a panel of trained judges assesses sensory quality. Results display that chitosan is more efficient reducing weight loss, respiration rate, and ethylene production. Both substances contribute to maintain flesh firmness, organoleptic characteristics and the fruits presentation.